Imaging modalities and treatment of paediatric upper tract urolithiasis: A systematic review and update on behalf of the EAU urolithiasis guidelines panel - Grivas, Nikolaos; Thomas, Kay; Drake, Tamsin; Donaldson, James; Neisius, Andreas; Petřík, Aleš; Ruhayel, Yasir; Seitz, Christian; Türk, Christian; Skolarikos, Andreas (Journal of pediatric urology, 2020)
BACKGROUND: Prompt diagnosis and treatment of paediatric urolithiasis are required to avoid long term sequelae of renal damage. OBJECTIVE: To systematically review the literature regarding the diagnostic imaging modalities and treatment approaches for paediatric urolithiasis. STUDY DESIGN: PubMed, Science Direct, Scopus and Web of Science were systematically searched from January 1980-January 2019. 76 full-text articles were included. RESULTS: Ultrasound and Kidney-Ureter-Bladder radiography are the baseline diagnostic examinations. Non-contrast Computed Tomography (CT) is the second line choice with high sensitivity (97-100%) and specificity (96-100%). Magnetic Resonance Urography accounts only for 2% of pediatric stone imaging studies. Expectant management for single, asymptomatic lower pole renal stones is an acceptable initial approach, especially in patients with non-struvite, non-cystine stones<7 mm. Limited studies exist on medical expulsive therapy as off-label treatment. Extracorporeal shock wave lithotripsy (SWL) is the first-line treatment with overall stone free rates (SFRs) of 70-90%, retreatment rates 4-50% and complication rates up to 15%. Semi-rigid ureteroscopy is effective with SFRs of 81-98%, re-treatment rates of 6.3-10% and complication rates of 1.9-23%. Flexible ureteroscopy has shown SFRs of 76-100%, retreatment rates of 0-19% and complication rates of 0-28%. SFRs after first and second-look percutaneous nephrolithotomy (PNL) are 70.1-97.3% and 84.6-97.5%, respectively with an overall complication rate of 20%. Open surgery is seldom used, while laparoscopy is effective for stones refractory to SWL and PNL. Limited data exist for robot-assisted management. CONCLUSIONS: In the initial assessment of paediatric urolithiasis, US is recommended as first imaging modality, while non-contrast CT is the second option. SWL is recommended as first line treatment for renal stones <20 mm and for ureteral stones<10 mm. Ureteroscopy is a feasible alternative both for ureteral stones not amenable to SWL as well as for renal stones <20 mm (using flexible). PNL is recommended for renal stones >20 mm.
Keywords: Kidney Calculi; dítě; Lithotripsy; Treatment Outcome; Practice Guidelines as Topic; Ureteral Calculi; ledvinové kameny; ureteroskopie; kameny v močovodu; Treatment; Urinary stones; Child; Urolithiasis; litotripse; výsledek terapie; Children; urolitiáza; směrnice pro lékařskou praxi jako téma; Diagnostic imaging; lidé; Humans; Ureteroscopy